Exploring the Influence of US Intervention in Syria - ATOUSSI , Abderraouf; NEFTI, Said (University of Eloued جامعة الوادي, 2024)
إن السياسة الخارجية لدولة ما هي تعبير عن مصالحها، فلا صداقة ولا عداوة دائمة، بل هناك مصالح دائمة، وللولايات المتحدة الأمريكية مصالح كثيرة في الشرق الأوسط عموماً وفي سوريا على وجه التحديد والتي تظهر من خلال تدخلاتها المختلفة. هدف هذا البحث هو استكشاف أثر هذه التدخلات على الشرق الأوسط، مع أخذ الحرب الأهلية السورية كعينة. وقد استخدمت الدراسة الحالية منهجًا تاريخيًا وصفيًا وتحليليًا يقيّم تاريخيًا ويقدم تفسيرًا دقيقًا وموضوعيًا وديناميكيًا للتدخل الأمريكي. وخلصت نتائج المذكرة إلى أن التدخل الأمريكي السري والعلني على حد سواء ترك سوريا مدمرة ومنهكة. كما أن التحول نحو الاعتماد على الفاعلين المحليين والوكلاء والحلفاء بدلاً من نشر قوات كبيرة جعل من السهل على الولايات المتحدة ضرب عصفورين بحجر واحد؛ إذ استطاعت توفير الحماية لمصالحها إلى جانب تقليل الخسائر البشرية في صفوف قواتها في المنطقة، ناهيك عن تجنب الاتهامات بالتورط الكبير. لقد مكنت الحرب الأهلية في سوريا الولايات المتحدة من تحقيق أهدافها العلنية والسرية في آن واحد، متخذة من هذه الرحب سبباً واحداً كبيراً يندرج تحت عنوان” الحرب ضد الإرهاب “لإنهاء أو على الأقل تقليل تهديدات تنظيم داعش في الشرق الأوسط The foreign policy of a country is an expression of its interests, as there is neither friendship nor permanent enmity, rather there is a permanent interest. The United States has many interests in The Middle East generally and Syria specifically. This research's purpose is to explore the impact that these interventions have on the Middle East, taking the Syrian civil war as a sample. The present study uses a historical, descriptive and analytical approach which historically assesses and provides a rigorous, objective and dynamic explanation of the involvement. The dissertation findings show that both covert and overt US involvement left Syria devastated and exhausted. The shift towards the reliance on local non-state actors, proxies and allies rather than large troop deployments made it easy for the US to kill two birds with one stone; being able to provide protection for its interests besides the minimization of casualties among its troops in the region, let alone avoiding the accusations of great involvement. The civil war in Syria enabled the US to fulfil its outright and secret objectives, adopting one great reason that lies under the title of " War against Terrorism" to end or at least decrease the threats of ISIS in the Middle East.
Literature and Civilization
Keywords: : السياسة الخارجية الأمريكية، سوريا، التدخل، التأثير، الإرهاب; The impact; The intervention; The Involvement; Syria; US foreign policy.